2007
DOI: 10.1086/522972
|View full text |Cite
|
Sign up to set email alerts
|

Rectal versus Intravenous Quinine for the Treatment of Childhood Cerebral Malaria in Kampala, Uganda: A Randomized, Double-Blind Clinical Trial

Abstract: Background. Although artemesinin derivatives are promising for the treatment of severe Plasmodium falciparum malaria, intravenous quinine remains the most affordable treatment. However, administration of intravenous quinine is often not feasible in rural areas in Africa because of the lack of simple equipment or trained staff. We compared the efficacy and safety of intrarectal quinine with those of intravenous quinine in the treatment of childhood cerebral malaria.Methods. In a randomized, double-blind clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 21 publications
0
21
1
Order By: Relevance
“…A recent survey in Uganda found that rectal artemisinins were available in only 5% of the health facilities despite the fact that this is the recommended pre-referral drug [78]. A feasible alternative is rectal quinine, which has been found to have comparable efficacy with intravenous quinine in the management of severe malaria in children [79-84] (Table 2) and could play a more significant role than currently acknowledged as pre-referral treatment for severe malaria. More recent studies in Senegal and Mali provide additional support for the efficacy and feasibility of this route and also show that a pre-referral kit of rectal quinine was acceptable to both caretakers and health workers [85,86].…”
Section: Quinine In the Management Of Severe Malariamentioning
confidence: 99%
“…A recent survey in Uganda found that rectal artemisinins were available in only 5% of the health facilities despite the fact that this is the recommended pre-referral drug [78]. A feasible alternative is rectal quinine, which has been found to have comparable efficacy with intravenous quinine in the management of severe malaria in children [79-84] (Table 2) and could play a more significant role than currently acknowledged as pre-referral treatment for severe malaria. More recent studies in Senegal and Mali provide additional support for the efficacy and feasibility of this route and also show that a pre-referral kit of rectal quinine was acceptable to both caretakers and health workers [85,86].…”
Section: Quinine In the Management Of Severe Malariamentioning
confidence: 99%
“…Despite this widespread use, data on quinine efficacy are limited. Two previous studies conducted in pediatric populations provide evidence of good efficacy in the management of cerebral malaria (Aceng et al, 2005; Achan et al, 2007). However, in another recent Ugandan study, 23% of children with uncomplicated malaria experienced genotype-corrected recrudescence within 28 days after quinine treatment, compared to no failures after AL treatment (Achan et al, 2009).…”
Section: Malaria Control In Ugandamentioning
confidence: 99%
“…Intramuscular administration may also be utilized, but is associated with complications including sterile abscess formation and sciatic nerve paralysis. Another option is rectal administration, which has shown good efficacy (Achan et al, 2007). Due to limitations in administration, length of treatment, tolerability, and efficacy, replacements for quinine for the treatment of severe malaria are of interest.…”
Section: Malaria Control In Ugandamentioning
confidence: 99%
“…Despite the associated adverse effects, quinine is still second-line treatment regimen and a drug of choice for severe malaria in Uganda. 18 Most of the quinine regimens recommended by various countries provide plasma concentrations ranging between 3.5 and 10.0 mg/mL, 17 concentrations favorable for cinchonism. Inadequate treatment with quinine, in most cases, results from fear for quinine toxicity, and nonadherence is one of the major causes for emergency of parasite resistance to the drug.…”
Section: Introductionmentioning
confidence: 99%